The Influence of Promotions, Service Features, Perception of Convenience, Perception of Benefits and Perception of Security on the Decision to Use Gopay E-Wallet - Kencanawati, Mella Sri; Anggraini, Reni; Tesniwati, Rini; Fitriyani, Desy (Score: Jurnal Lentera Manajemen Pemasaran, 2024)
E-wallet is an application connected to the internet that can store nominal money. E-Wallets in Indonesia, one of which is the Gopay E-Wallet, is an all-in-one digital wallet belonging to the giant Indonesian start-up, Gojek, which can be used from fast transactions for all Gojek services, to sending or receiving money easily. This study aims to determine the effect of the variables Promotion, Service Features, Perceived Convenience, Perceived Benefits and Perceived Security on the Decision to Use Gopay E-Wallet in Tangerang City. The population of this study is respondents who use Gopay E-Wallet and have made purchases using Gopay E-Wallet in Tangerang City at least once. The sample used was 120 respondents, non-probability sampling method and the technique used was purposive sampling. Using primary data obtained using a questionnaire. The test phases carried out are Validity Test, Reliability Test, Classical Assumption Test namely Normality Test, Multicollinearity Test, and Heteroscedasticity Test, and use Multiple Linear Regression Test, after that test the hypothesis with T test and F test, and R^2 test (Coefficient determination). The testing tool was carried out using SPSS. The results of the F Test show that the variables Promotion, Service Features, Perceived Convenience, Perceived Benefits and Perceived Security have a simultaneous effect on the Decision to Use Gopay E-Wallet. The results of the T-test show that the variables Promotion, Service Features, Perceived Benefits and Perceived Security partially influence the Decision to Use Gopay E-Wallet, while the Perceived Convenience variable does not affect the Decision to Use Gopay E-Wallet.